Overexpression of a Transcription Factor Increases Lipid Content in a Woody Perennial Jatropha curcas - Ye, Jian; Wang, Chunming; Sun, Yanwei; Qu, Jing; Mao, Huizhu; Chua, Nam-Hai (Frontiers in Plant Science, 2018)
Vegetable oil is an important renewable resource for dietary consumption for human and livestock, and more recently for biodiesel production. Lipid traits in crops are controlled by multiple quantitative trait loci (QTLs) and each of them has a small effect on lipid traits. So far, there is limited success to increase lipid yield and improve lipid quality in plants. Here, we reported the identification of a homolog of APETALA2-transcription factor WRINKLED1 (JcWRI1) from an oleaginous plant Jatropha curcas and characterized its function in Jatropha and Arabidopsis thaliana. Using physical mapping data, we located JcWRI1 in a QTL region specifying high oleate and lipid content in Jatropha. Overexpression of JcWRI1 in Jatropha elevated seed lipid content and increased seed mass. Lipid profile in seeds of over-expression plants showed higher oleate content which will be beneficial to improve biodiesel quality. Overexpression of JcWRI1 activated lipid-related gene expression and JcWRI1 was shown to directly bind to the AW-box of promoters of some of these genes. In conclusion, we were able to increase seed lipid content and improve seed lipid quality in Jatropha by manipulating one key transcription factor JcWRI1.